2016
DOI: 10.1080/2093761x.2016.1152204
|View full text |Cite
|
Sign up to set email alerts
|

Urban microclimate and thermal comfort modelling: strategies for urban renovation

Abstract: a planning and urban design, university of bío-bío, concepción, chile; b urbanism and territory government, technical university of madrid, madrid, Spain ABSTRACTThe urban microclimate plays an important role in building energy consumption and thermal comfort in outdoor spaces. Nowadays, cities need to increase energy efficiency, reduce pollutant emissions and mitigate the evident lack of sustainability. In light of this, attention has focused on the bioclimatic concepts use in the urban development. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 36 publications
0
11
0
2
Order By: Relevance
“…They showed that the higher the H/W ratio, the lower the air temperature. They also proved the positive impact of building height on the value of the thermal comfort indicator in the summer [7,[10][11].…”
Section: Figmentioning
confidence: 79%
“…They showed that the higher the H/W ratio, the lower the air temperature. They also proved the positive impact of building height on the value of the thermal comfort indicator in the summer [7,[10][11].…”
Section: Figmentioning
confidence: 79%
“…Climate conditions in urban regions differ from rural areas, with greater temperatures, less diurnal temperature fluctuation, changes in wind direction and speed, altered heat transmission, and an outstanding rainfall balance. This phenomenon, known as the urban microclimate, has a variety of significant consequences on city sustainability [142].…”
Section: • Energy Balance Approachmentioning
confidence: 99%
“…Simulating people's average height and outdoor activities, the air temperature, relative humidity and wind speed at a height of 1.5 m above the ground were measured. 17,18…”
Section: Envi-met Numerical Simulationmentioning
confidence: 99%